The resettlement of British Columbia essays on colonialism and geographical change - Harris, Richard Cole 1939- (UBC Press, 1997)
In this beautifully crafted collection of essays, Cole Harris reflect on the strategies of colonialism in British Columbia during the first 150 years after the arrival of European settlers. The pervasive displacement of indigenous people by the newcomers, the mechanisms by which it was accomplished, and the resulting effects on the landscape social life, and history of Canada's western-most province are examined through the dual lenses of post-colonial theory and empirical data. By providing a compelling look at the colonial construction of the province, the book revises existing perceptions of the history and geography of British Columbia.